(untitled) (Current Problems in Rail Vehicles, 2021)
This paper deals with phenomena called torsional oscillations of powered wheelsets which occur in modern railway vehicles, particularly locomotives. The paper is focused on relation between mechanical and electrical part of locomotives drives especially in situation when wheelset oscillates in torsional direction. Mathematical model of the drive was used for determining of the wheelsets state (does not oscillate or oscillates) which is followingly used as an additional input for torque control. This is done for the sake of reduction of oscillations that may have negative impact for durability of the vehicle.